2020
DOI: 10.1155/2020/8881687
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Associated lncRNAs: Promising Targets for Neurological Disease Diagnosis and Therapy

Abstract: Neurological diseases are a major threat to global public health and prosperity. The number of patients with neurological diseases is increasing due to the population aging and increasing life expectancy. Autophagy is one of the crucial mechanisms to maintain nerve cellular homeostasis. Numerous studies have demonstrated that autophagy plays a dual role in neurological diseases. Long noncoding RNAs (lncRNAs) are a vital class of noncoding RNAs with a length of more than 200 nucleotides and cannot encode protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 106 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…miR-19a and miR-19b representative validated target genes of miR-19a and miR-19b are shown in Table 3A–C . Phosphatase and Tensin Homolog (PTEN), 21 , 22 Rap Guanine Nucleotide Exchange Factor (2Rapgef2), 23 voltage-gated potassium channel subunits, 20 Tumor Protein p53 (p53), 24 and RUNX Family Transcription Factor 3 (RUNX3) 25 are common targets shared by both miR-19a and miR-19b. Further, miR-19a has its own validated targets including Suppressor of Cytokine Signaling 1 (SOCS1), Methyl-CpG Binding Protein 2 (MeCP2), Ras Homolog Family Member B (RhoB), Peroxisome Proliferator Activated Receptor Alpha (PPARα), and Leucine Rich Repeats and Immunoglobulin Like Domains 1 (LRIG1).…”
Section: Resultsmentioning
confidence: 99%
“…miR-19a and miR-19b representative validated target genes of miR-19a and miR-19b are shown in Table 3A–C . Phosphatase and Tensin Homolog (PTEN), 21 , 22 Rap Guanine Nucleotide Exchange Factor (2Rapgef2), 23 voltage-gated potassium channel subunits, 20 Tumor Protein p53 (p53), 24 and RUNX Family Transcription Factor 3 (RUNX3) 25 are common targets shared by both miR-19a and miR-19b. Further, miR-19a has its own validated targets including Suppressor of Cytokine Signaling 1 (SOCS1), Methyl-CpG Binding Protein 2 (MeCP2), Ras Homolog Family Member B (RhoB), Peroxisome Proliferator Activated Receptor Alpha (PPARα), and Leucine Rich Repeats and Immunoglobulin Like Domains 1 (LRIG1).…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs are highly expressed in mammalian brains and are linked with brain development and function [13]. Recent studies have found that lncRNA is abnormally expressed in PD patients, suggesting that lncRNA may serve the purpose of regulating the onset and advancing of PD [14].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are transcripts with a length of more than 200 nucleotides without protein coding function. LncRNAs have involved in biological processes as an important role, such as proliferation, differentiation, apoptosis, invasion, and metastasis of cancer [13,14].Recently, growing evidence indicated that lncRNAs primarily participant in the occurrence and development of cancer, which may related to its potential of regulating autophagy [15,16].Thus, developing prognostic biomarker related to autophagy for PC patients may be helpful in treatment and prognosis of PC.…”
Section: Introductionmentioning
confidence: 99%